2004
DOI: 10.1529/biophysj.104.040519
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Correlation Spectroscopy Relates Rafts in Model and Native Membranes

Abstract: The lipid raft model has evoked a new perspective on membrane biology. Understanding the structure and dynamics of lipid domains could be a key to many crucial membrane-associated processes in cells. However, one shortcoming in the field is the lack of routinely applicable techniques to measure raft association without perturbation by detergents. We show that both in cell and in domain-exhibiting model membranes, fluorescence correlation spectroscopy (FCS) can easily distinguish a raft marker (cholera toxin B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
254
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(293 citation statements)
references
References 46 publications
36
254
2
1
Order By: Relevance
“…Additionally, microfilament depolymerization can disrupt lipid rafts (Bacia et al, 2004). The latter finding is of particular interest, since it has been reported that 16E5 induces complete disassembly of microfilaments in mouse fibroblasts (Thomsen et al, 2000).…”
Section: E5-induced Redistribution Of Ganglioside Gm1 Is Not Mediatmentioning
confidence: 96%
“…Additionally, microfilament depolymerization can disrupt lipid rafts (Bacia et al, 2004). The latter finding is of particular interest, since it has been reported that 16E5 induces complete disassembly of microfilaments in mouse fibroblasts (Thomsen et al, 2000).…”
Section: E5-induced Redistribution Of Ganglioside Gm1 Is Not Mediatmentioning
confidence: 96%
“…From a variety of possible probes we stringently selected those that at steady state showed mainly apical membrane localization on polarized MDCK cells with no staining of the endoplasmic reticulum or other organelles close to the plasma membrane. FRAP experiments were routinely performed at room temperature (Ϸ25°C) to minimize membrane deformations caused by temperature gradients and the influence of membrane traffic events on fluorescence recovery (31). The apparent diffusion coefficient D and the percentage recovery were derived from the fluorescence intensity at ''infinite'' time after photobleaching, I ϱ , calculated by the theoretical fit (25,26) and not from a visual examination of the experimental curves that were rarely followed until recovery was complete.…”
Section: Resultsmentioning
confidence: 99%
“…FCS is a method that has been extensively used and further developed by our group, being introduced and established as a very suitable approach to characterize model and cellular membranes (Schwille et al 1999a;Bacia et al 2004). It is, in a way, a single-molecule method, but provides sufficient statistical significance to also use it for general characterization of membranes, mainly through the diffusion properties of their constituents.…”
Section: Fluorescence Correlation Spectroscopy (Fcs)mentioning
confidence: 99%